Vr: Time machine - Polydorou, Doros; Ben-Tal, Oded; Damsma, Atser; Schlichting, Nadine (My University, 2020)
Time Machine is an immersive Virtual Reality installation that explains – in simple terms – the Striatal Beat Frequency (SBF) model of time perception. The installation was created as a collaboration between neuroscientists within the field of time perception along with a team of digital designers and audio composers/engineers. This paper outlines the process, as well as the lessons learned, while designing the virtual reality experience that aims to simplify a complex idea to a novice audience. The authors describe in detail the process of creating the world, the user experience mechanics and the methods of placing information in the virtual place in order to enhance the learning experience. The work was showcased at the 4th International Conference on Time Perspective, where the authors collected feedback from the audience. The paper concludes with a reflection on the work and some suggestions for the next iteration of the project.
Keywords: Immersion; Installation; Time perception; Virtual Reality